2022
DOI: 10.3390/ijms232012708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacies of FLT3 Inhibitors in Patients with Acute Myeloid Leukemia

Abstract: FLT3 mutations are the most common genomic alteration detected in acute myeloid leukemia (AML) with a worse clinical prognosis. The highly frequent FLT3 mutations, together with the side effects associated with clinical prognosis, make FLT3 promising treatment targets and have provoked the advancement of FLT3 inhibitors. Recently, numerous FLT3 inhibitors were actively developed, and thus the outcomes of this aggressive subtype of AML were significantly improved. Recently, midostaurin and gilteritinib were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…132 Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest. 133 In 2023, Yashar et al reported that combining an LSD1 inhibitor GSK-2879552 and an FLT3 inhibitor Quizartinib exhibited a synergistic effect in inducing cell death in FLT3 mutant AML (Table 2). 101 This drug combination simultaneously disrupted the binding of STAT5, LSD1, and GFI1 from the MYC blood superenhancer complex, leading to the repression of MYC expression and causing the accumulation of repressive H3K9me1 at MYC target genes.…”
Section: Combination Of Lsd1 Inhibitor and Flt3mentioning
confidence: 99%
See 1 more Smart Citation
“…132 Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest. 133 In 2023, Yashar et al reported that combining an LSD1 inhibitor GSK-2879552 and an FLT3 inhibitor Quizartinib exhibited a synergistic effect in inducing cell death in FLT3 mutant AML (Table 2). 101 This drug combination simultaneously disrupted the binding of STAT5, LSD1, and GFI1 from the MYC blood superenhancer complex, leading to the repression of MYC expression and causing the accumulation of repressive H3K9me1 at MYC target genes.…”
Section: Combination Of Lsd1 Inhibitor and Flt3mentioning
confidence: 99%
“…In recent years, targeting FLT3 has been an integral component of treatment regimens for FLT3-ITD/TKD-mutated AML patients, leading to significantly extended survival rates . Despite the clinical availability of FLT3 inhibitors, their impact on survival outcomes remains modest …”
Section: Combination Of Lsd1 Inhibitors and Other Target-based Inhibi...mentioning
confidence: 99%
“…Upon maturation into lymphoid or myeloid cells, the expression of FLT3 is either reduced or lost altogether. The receptor comprises five immunoglobulin-like domains in the extracellular region, a juxtamembrane (JM) domain, a tyrosine kinase domain (TKD) divided by a kinase insert domain, and a C-terminal domain in the intracellular region [2,5,6]. The structure of FLT3 is shown in Figure 1.…”
Section: Flt3 Structurementioning
confidence: 99%
“…These inhibitors aim to counteract the aberrant signaling pathways triggered by FLT3 mutations, thereby hindering the growth and survival of leukemia cells [32]. The integration of FLT3 mutational status into the risk strati cation of AML patients has become essential for treatment decision-making [33]. The identi cation of FLT3 mutations not only informs prognosis but also guides the selection of targeted therapies, fostering a more personalized and effective approach to managing AML [34].…”
Section: Introductionmentioning
confidence: 99%